Body composition, physical fitness and exercise activities of elderly - Ruiz-Montero, Pedro Jesús; Castillo-Rodríguez, Alfonso (Journal of Physical Education and Sport, 2017)
Ageing is a natural and inevitable process with degenerative changes in most of the physical, physiological, psychological and social functions. Furthermore, the ageing process has an impact on the body composition and physical fitness of elderly people. Changes in body composition are considered one of the major causes of chronic diseases of ageing people. In addition, body composition is an important marker of health and predictor of comorbidities. Hence, from a clinical point of view, it is interesting to appreciate the changes through variations in body composition while age is linearly increasing because the states of body composition are related to the ageing. Furthermore, the association between physical fitness and physical activity and the benefits this provides for elderly people has been explained in great detail in several studies. The main objective of exercise is the improvement or maintenance of physical fitness. Exercise produces benefits in the mobility of elderly people and is effective in the treatment and prevention causes of morbidity and mortality. In conclusion, there is a general opinion in the literature about the changes of body composition in elderly people and the benefits of exercise on physical fitness and control of body composition. Therefore, higher emphasis might be focused in the improvement of ageing and body composition in elderly people through the practice of physical exercise.
Keywords: fat mass; fat-free mass; physical activity; prevention; Scopus